2018
DOI: 10.1111/iere.12288
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent Taxes With Endogenous Human Capital Formation

Abstract: We assess the gains attained by the introduction of age-dependent labor income taxes in an overlapping generations economy where individuals live a meaningful life cycle and endogenously accumulate human capital. The model is sufficiently rich to isolate the role of general equilibrium effects, credit market imperfections, and different forms of human capital accumulation. The large welfare gains we obtain cannot be attained without age dependence, nor can they be attained with age-dependent taxes if progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Previous literature has pointed out that the existence of individual‐specific taxation could generate welfare gains in the implementation of fiscal policies in the presence of consumption externalities (Jacobs & de Mooij, 2015; Kaplow, 2012). As mentioned in Section 1, recent research has also indicated that age‐dependent labor income taxation in economies with OLGs could reduce the costs associated with distortionary fiscal policy (Bastani et al, 2013; Blomquist & Micheletto, 2008; Da Costa & Santos, 2018; Gervais, 2012; Weinzierl, 2011). To understand the role of age‐dependent labor income taxes in the setting of optimal climate and fiscal policy when there are production externalities, as special cases, I consider a policy with age‐dependent taxation under different assumptions about separability and nonseparability in preferences on consumption and leisure.…”
Section: The Role Of Preferences and Labor Income Taxationmentioning
confidence: 99%
“…Previous literature has pointed out that the existence of individual‐specific taxation could generate welfare gains in the implementation of fiscal policies in the presence of consumption externalities (Jacobs & de Mooij, 2015; Kaplow, 2012). As mentioned in Section 1, recent research has also indicated that age‐dependent labor income taxation in economies with OLGs could reduce the costs associated with distortionary fiscal policy (Bastani et al, 2013; Blomquist & Micheletto, 2008; Da Costa & Santos, 2018; Gervais, 2012; Weinzierl, 2011). To understand the role of age‐dependent labor income taxes in the setting of optimal climate and fiscal policy when there are production externalities, as special cases, I consider a policy with age‐dependent taxation under different assumptions about separability and nonseparability in preferences on consumption and leisure.…”
Section: The Role Of Preferences and Labor Income Taxationmentioning
confidence: 99%
“…Third, the benefit derived by an ordinary type 1 or type 2 agent from mimicking a type 0 agent is entirely confined to the first period, as it is assumed that these mimickers obtain employment according to their actual (already realized) productivity in the second period. 21 Given the above discussion, to prevent an ordinary type 1 worker from mimicking type 0 workers in education or public employment, we require that he/she obtains a weakly higher period-1 utility when working as compared to enrolling in education or public employment, by imposing the following constraints:…”
Section: The Governmentmentioning
confidence: 99%
“…In the numerical simulations, we impose(22) as a weak inequality and(23) in its full form as we cannot guarantee that(22) is binding under all possible parameter constellations 21. Given that education effort, in principle, could serve as a signal of worker ability, we assume that the minimal effort level e is sufficiently large so that it does not deter firms from remunerating ordinary type 1 and 2 workers according to their actual (already realized) productivity in the second period.…”
mentioning
confidence: 99%
“…in the first and second periods, and (ii) a potential transfer in the third period via the lump sum component of the function 𝑇 3 (•).28 In other words, a general savings tax plays the same role as a pension system. By using 𝜇 4 to denote the Lagrange multiplier associated with the self-selection constraint (23), the policy rule for the education transfer is presented in proposition 5.…”
Section: Optimal Education Policymentioning
confidence: 99%
“…It can easily be shown that an increase in 𝑐 𝐸 increases the number of type 0 individuals with innate productivity 𝜃 1 in the education state, as well as the number of type 0 individuals with innate productivity 𝜃 2 in both education states (𝐸 1 and 𝐸 2 ), with an exactly corresponding decrease in the number of people in unemployment and public employment. Therefore, if the self-selection constraint (23) is not binding (i.e. 𝜇 4 = 0), a sufficient condition for the right-hand side of the equation ( 55) to be negative would be the following:…”
Section: Optimal Education Policymentioning
confidence: 99%